2021
DOI: 10.1590/1413-81232021266.26392018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between level of education and moral judgment toward who abuse drugs

Abstract: The aim of the present study is to verify the differences of the moral judgment toward the people who abuse drugs according to the schooling of the participants. This is the Brazilian part of a multicentric study. N=180 individuals in a community in Brasília, DF, Brazil; following consent, descriptive data were collected by anonymous interviewer-administered questionnaire that included socio-demographic, educational level and the history of drug use. Participants were predominantly females, middle-aged, marrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Every adult, family member, health professional, teacher, or community representative plays an important role when it comes to providing guidelines to adolescents by giving them opportunities for the acquisition of information, and contributions to make these students more skilled and more able to lead a quality life (Elicker, Palazzo, Aerts, Alves, & Câmara, 2015). A study that verified differences in moral judgment regarding people that do drugs according to the level of education of the participants identified that the participants with higher level of education tend to have more positive, less stigmatizing attitudes regarding drug users, which reinforces the role played by teachers as fundamental in the support provided and the change in the ways to approach adolescent students that use illegal substances (Gallassi, Oliveira, Silva, Machado, & Wagner, 2021).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Every adult, family member, health professional, teacher, or community representative plays an important role when it comes to providing guidelines to adolescents by giving them opportunities for the acquisition of information, and contributions to make these students more skilled and more able to lead a quality life (Elicker, Palazzo, Aerts, Alves, & Câmara, 2015). A study that verified differences in moral judgment regarding people that do drugs according to the level of education of the participants identified that the participants with higher level of education tend to have more positive, less stigmatizing attitudes regarding drug users, which reinforces the role played by teachers as fundamental in the support provided and the change in the ways to approach adolescent students that use illegal substances (Gallassi, Oliveira, Silva, Machado, & Wagner, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…Although they understand the complexity of the phenomenon by listing risk factors that contribute to the use of alcohol and other drugs, the teachers still perceive students who use drugs as "morally weak", "a danger to society" and that "they could commit small crimes in their families". Such situation could be characterized as stigma, understood as a social construction, which attributes to its beholder a status of devaluation by other members of society (Gallassi et al, 2021). These situations take place when individuals are identified and related to some undesirable characteristic that they possess, and because of that, they get discriminated and underrated by society.…”
Section: These Data Are Different From What Was Found In Thementioning
confidence: 99%
“…The literature reports the desire of the people experiencing SUD to change their lives and solve their problems related to this drug use (Pettersen et al, 2019;Worley, 2017). However, the stigma associated with SUD can delay seeking help, which occurs when several domains of people's lives are already affected (Brown, 2011;Gallassi et al, 2021;Crapanzano et al, 2019). Thus, when seeking treatment, they often have additional social and health problems, including mental disorders, unemployment, poor housing, and some justice involvement (Daley, 2013;Dir et al, 2022;Reif et al, 2014), which systemically compromising their SF.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda que entendam a complexidade do fenômeno ao elencarem os fatores de risco que contribuem para o uso de álcool e outras drogas, os professores percebem os alunos que fazem uso como "moralmente fracos", "um perigo para a sociedade" e que "poderiam cometer delitos na sua família". Tal situação pode ser caracterizada como estigma, entendido como uma construção social, a qual atribui ao seu portador um status de desvalorização em relação aos outros membros da sociedade (Gallassi et al, 2021). Essas situações ocorrem quando os indivíduos são identificados em relação a alguma característica indesejável que possuem e, a partir disso, são discriminados e desvalorizados pela sociedade.…”
Section: Discussionunclassified
“…Cada adulto, familiar, profissional de saúde, professor, representante da comunidade, tem importante papel na orientação do adolescente oferecendo-lhe a oportunidade da informação, contribuindo para que se torne habilitado e capaz de cuidar de sua vida com qualidade (Elicker, Palazzo, Aerts, Alves, & Câmara, 2015). Um estudo que verificou as diferenças do julgamento moral em relação às pessoas que usam drogas de acordo com a escolaridade dos participantes, identificou que os mais escolarizados tendem a ter atitudes mais positivas e menos estigmatizantes com relação aos usuários, o que reforça o papel de professores como fundamental no processo de acolhimento e mudança na abordagem de estudantes adolescentes que estão em uso de substâncias (Gallassi, Oliveira, Silva, Machado, & Wagner, 2021).…”
Section: Introductionunclassified